The Effect of Group Counseling Through the Solution Focused Brief Counseling (SFBC) Approach to Improving Adolescent Emotional Management - Bima Ardiyanza; Indiati; Astiwi Kurniati (Urecol Journal. Part H: Social, Art, and Humanities, 2022)
This study aims to examine the effect of group counseling through a solution focused brief counseling (sfbc) approach to improve adolescent emotional management. This study uses the one group pretest-posttest design. The samples taken in study were 8 teenagers consisting of one experimental group. Sampling using an emotion management questionnare. The data analysis method used is parametric analysis paired sample t-test. The results of this study indicate that group counseling through a solution focused brief counseling (sfbc) approach has an effect on on improving adolescent emotional management. This evidenced from the results of the paired sample t-test with a probability value of sig (2-tailed) 0,000 < 0,05. Based on the results of the analysis and discussion, there is a difference in the average score of the emotional management questionare 12,90% from the results of pretest and posttest. The results of the research can be concluded that group counseling through a solution focused brief counseling (sfbc) approach has an effect on improving adolescent emotional management.